Correlations among thermophysical properties, ignition quality, volatility, chemical composition, and kinematic viscosity of petroleum distillates. (1st January 2016) - Shen, Jun; Astrath, Nelson G.C.; Pedreira, Paulo R.B.; Guimarães, Francine B.; Gieleciak, Rafal; Wen, Qing; Michaelian, Kirk H.; Fairbridge, Craig; Malacarne, Luis C.; Rohling, Jurandir H.; Baesso, Mauro L.
Highlights: Thermophysical properties, dn/dT and D, are correlated with other distillate properties. PLS analysis of Raman spectra shows that molecular components affect − dn/dT values. dn/dT and D exhibit considerable promise as fuel quality indicators. Abstract: Thermophysical measurements and Raman spectroscopy were utilized to investigate 17 hydrocarbon distillates derived from Canadian oil sands in this work. Thermal lens and optical interferometer techniques were used to determine the thermal diffusivity ( D ) and temperature coefficient of the refractive index ( dn/dT ), respectively. It was found that D and dn/dT are closely correlated with the cetane numbers, distillation temperatures, monocyclic aromatics contents, and kinematic viscosities of the fuels. Raman spectra yielded information on the chemical compositions of the distillates, with aromatic contents proving to be particularly relevant. Multivariate analysis elucidated the relationships among the samples, their properties according to ASTM analyses, and the influence of composition on D and dn/dT .